Komitmen Organisasional dan Authentic Happiness: Studi Kasus Karyawan Pada Sebuah Organisasi Bisnis Retail di Kota Bandung - Sherlywati Sherlywati (Jurnal Administrasi Bisnis, 2015)
This research was initially exploring the relationship between the Authentic Happiness-The Source of Happines and Organizational Commitment. The concept of Authentic Happiness is derived from the Positive Psychology-Authentic Happiness proposed by Seligman. Meanwhile the concept of organizational commitment is taken from Meyer and Allens Organizational Commitment. The research questions are twofolds. Firstly, whether three sources of happiness are correlated with three dimensions of organizational commitment. Secondly, whether demographic factors are accounted at explaining organizational commitment. Fifty-four (54) employees of a leading retail company in Bandung were interviewed and surveyed using online instrument, as many as 48 turned out with valid responds. Collected data were processed and analyzed using simple statistics, such as descriptive statistics, Pearson’s Product Moment and Alpha Cronbach to test data validity and reliability. Meanwhile to do correlation test, crosstabs-chi square and Pearsons Correlation was used. The research reveals that the Source of Happiness has strong to mild positive correlation with Organizational Commitment. This research also confirms the existing findings that demographic characteristics i.e. gender and length of work has a positive relationship with organizational commitment. Keywords: organizational commitment, positive psychology, authentic happiness Abstrak Penelitian ini mencoba mengeksplorasi hubungan antara Sumber Kebahagiaan - Authentic Happiness dan Komitmen Organisasional. Konsep Authentic Happiness berasal dari positif psikologi yang diperkenalkan oleh Seligman. Sedangkan konsep komitmen organisasional diambil dari Meyer dan Allen. Pertanyaan utama peneli- tian ini ada dua, pertama apakah dari ketiga sumber kebahagiaan berkorelasi dengan ketiga dimensi komitmen organisasional. Kedua, apakah faktor demografi responden dapat menjelaskan komitmen organisasional karyawan. Lima puluh empat karyawan dari sebuah perusahaan ritel terkemuka di Bandung diwawancarai dan disurvey menggunakan alat kuesioner online dan kuesioner manual. Sebanyak 48 responden merespon kuesioner dengan valid. Data dianalisa dan diolah menggunakan statistik sederhana, seperti statistik deskristif, Pearson Product Moment, Alpha Cronbach, Crosstabs-Chi Square, dan Pearson Correlation. Hasil penelitian mengungkapkan bahwa sumber kebahagiaan memiliki korelasi dengan komitmen organisasi karyawan. Dan ditegaskan dalam penelitian ini bahwa, demografi karakteristik gender dan lama kerja memiliki hubungan positif dengan komitmen organisasi. Kata Kunci : komitmen organisasi, psikologi positif, authentic happiness